Science Learning Based on The Sasak Tribe Tradition to Develop Student Entrepreneurial Attitudes - Hikmawati Hikmawati; I Made Sutajaya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2021)
Entrepreneurial attitude needs to be developed as early as possible so that students have the provision of life skills in the future. Students are expected to become job creators or entrepreneurs when they graduate from school so that students can quickly respond to changes. The purpose of this study was to analyze the science learning based on the Sasak tradition to develop students' entrepreneurial attitudes. The research method used is literature review derived from articles in national and international scientific journals. The results of the literature review show that entrepreneurial attitudes that can be developed include: achievement motivation, taking advantage of opportunities, being creative, innovating, committed, responsible, and independent. One of the science learning models that can facilitate the development of students' entrepreneurial attitudes is the 6E learning cycle model (Engage, Explore, Explain, Elaborate, Exhibit, Evaluate). This model can be related to the traditions of the Sasak tribe, such as weaving typical Lombok cloths that utilize the concept of substances and their characteristics, and making traditional snacks using conventional biotechnology concepts. An entrepreneurial attitude can be developed at each stage, especially at the Exhibit stage, students can exhibit products that have a selling value, such as Sukarara woven cloth and jajan poteng reket. Thus, science learning based on the Sasak tradition is expected to be a strong foundation for further education and to shape the entrepreneurial spirit of students so that they become a generation of superior and character.